About the Greek origin of acarology: a short note on Argas and the Acari - Zaborowski, Robert; Daszkiewicz, Piotr (Biological Letters, 2017)
The article presents the etymology and Greek roots of two terms in modern acarology. The origin of acarological nomenclature is analysed in the context of Homer’s Odyssey and Aristotle’s Parts of Animals and History of Animals. The Greek concept of the smallest animals “acari” as indivisible has been influencing European culture for centuries. The article shows the influence of the Greek tradition on zoology in the 18th century, at the time of birth of modern acarology. The works of French naturalists, the founders of this science, are analysed in this context.